A Review of Holding Company on Semarang Regional Government Owned Enterprise - Ahmad Malik; Ali Umar Dhani (Universal Business and Management Review, 2024)
The establishment of a holding company for regional government owned enterprises (BUMD) is one of the efforts that can be made to further improve the performance of regionally owned enterprises so that they can contribute more to regional original income. This research uses literature study, namely a series of activities related to methods of collecting library data, reading and taking notes, and managing research materials. In order to realize the objectives of establishing a BUMN Holding Company, in its implementation, it must be guided by the principles of Good Corporate Governance. Supervision (control) is required from all stake holders, especially the DPRD, both in the recruitment of the Board of Commissioners and the Board of Directors, as well as in carrying out the company's activities.